2021
DOI: 10.3390/antiox10010101
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adipose Tissue of Prediabetic and Diabetic Females Shares a Set of Similarly Upregulated microRNAs Functionally Annotated to Inflammation, Oxidative Stress and Insulin Signaling

Abstract: Hypertrophic and hypoxic visceral adipose tissue (VAT) secretes proinflammatory cytokines promoting insulin resistance (IR), prediabetes and type 2 diabetes (T2DM) microRNAs (miRNAs) are markers of metabolic disorders regulating genes critical for e.g., inflammation, glucose metabolism, and antioxidant defense, with raising diagnostic value. The aim of the current study was to evaluate whether hyperglycemia is able to affect the expression of selected miRNAs in VAT of prediabetic (IFG) and diabetic (T2DM) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
1
20
0
2
Order By: Relevance
“…Further, the effect seems to be postponed in time (alterations are significant mostly one stage after introducing HG). Overall, our data are in accordance with findings reported by Andersen et al [ 16 ] and partially support our earlier findings [ 5 , 7 , 60 ] that visceral Ads exhibit signs of metabolic memory. Obtained results suggest that miR-143-3p, miR-374-5p, and miR-152-3p may take part in preserving toxic effects of HG in Ads, however, the expression only of miR-152-3p may be related to genes analyzed in our study.…”
Section: Discussionsupporting
confidence: 94%
“…Further, the effect seems to be postponed in time (alterations are significant mostly one stage after introducing HG). Overall, our data are in accordance with findings reported by Andersen et al [ 16 ] and partially support our earlier findings [ 5 , 7 , 60 ] that visceral Ads exhibit signs of metabolic memory. Obtained results suggest that miR-143-3p, miR-374-5p, and miR-152-3p may take part in preserving toxic effects of HG in Ads, however, the expression only of miR-152-3p may be related to genes analyzed in our study.…”
Section: Discussionsupporting
confidence: 94%
“…miR-342-3p promotes the adipogenesis in mesenchymal stem cells by suppressing CtBP2 and releasing C/EBPα from CtBP2 binding ( 22 ). In the female patients with T2D and impaired fasting glucose (IFG), miRNAs including miR-342-3p were upregulated and in silico enrichment analyses suggested the 11 top differentially expressed miRNAs possibly involved in oxidative stress, inflammation and insulin signaling ( 23 ). In our study, miR-342-3p was prominently expressed in SVF of epididymal adipose tissue and we were interested in the status of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on KEEG analysis of miR-204-5p and its downstream predictive target genes and previous literature reports, it is concluded that miR-204-5p is associated with a variety of diseases related to the central nervous system [ 26 ]. Findings from previous reports revealed that miR-204-5p is involved in multiple signaling pathways and results from related studies have shown that miR-204-5p is involved with oxidative stress-related pathways, in specific to the oxidative capacity of mitochondria as demonstrated in vivo [ 27 29 ]. Accordingly, the potential role of miR-204-5p in depression became the focus of our research in this report.…”
Section: Discussionmentioning
confidence: 99%